A fractured inferior vena cava filter strut migrating to the left pulmonary artery. (2015) - Hudali, Tamer; Zayed, Ali; Karnath, Bernard
Abstract: Inferior vena cava filters are increasingly used in patients with recurrent venous thromboembolism who are contraindicated to anticoagulation. Migration of a broken strut to the pulmonary artery is a very rare complication of these filters. We report the case of an 83-year-old female who experienced this complication with the migratory strut remaining in the same position for years. This case provides evidence that such filters probably have higher rates of complications than what has been thought that remain asymptomatic. The indications and the management of complications of such devices need to be studied further.